The Influence of Financial Literacy, Work Experience, Parents' Socioeconomic Status on the Personal Financial Management of Accounting Education Students - Rohayati, Suci; Saputra, Irwan Adimas Ganda; Ghani, Erlane K (IKIP Widya Darma Surabaya, 2024)
Objectives: The role of students is expected to be able to improve the economy with good financial management patterns. This seems difficult to achieve because the financial literacy of youth age groups such as university students and school students is relatively low. Method: This research analyzes factors that influence students' personal financial management, such as financial literacy, work experience, and socio-economic status. This quantitative research used random sampling techniques with a sample size of 32 respondents. Data was collected using questionnaires and questionnaires which were then analyzed using multiple linear regression. Results: The research results show that financial literacy, work experience and parents' socio-economic status simultaneously or partially influence students' personal financial management. Novelty: This research focuses on accounting education students whose scientific basis is in accordance with financial literacy and is still rarely researched.